Investigation of the Prevalence of HBsAg, Anti-HCV, and Anti-HIV in a Prison in Turkey: A Point Prevalence Study. - Yılmaz, Esmeray Mutlu; Bilgin, Melek; Köksal, Zeynep Şentürk; Oruç, Muhammet Ali; Tabak, Fehmi (Viral Hepatitis Journal / Viral Hepatit Dergisi, 2023)
Objectives: Access to health services is more difficult for prison inmates than for the general population. This study aimed to determine the prevalence of hepatitis B surface antigen (HBsAg), anti-hepatitis C virus (HCV), and anti-human immunodeficiency virus (HIV) in prisoners and to determine the rates of risky behavior in terms of these viral diseases using a questionnaire. Materials and Methods: Nine hundred ninety-three prisoners participated in the Risky Behavior Questionnaire. On March 13-14, 2023, HBsAg, anti-HCV, and anti-HIV were studied by rapid tests in the fingertip blood of 553 volunteer prisoners. Positive samples were re-examined using ELISA. Results: Out of 1,490 inmates remaining in prison, 993 voluntarily participated in the survey study and 553 participated in the blood control. All participants included in the study were male. The median age was 36 (17-81). Of the participants, 26 (4.7%) HBsAg positivity and 7 (1.3%) anti-HCV positivity were detected. Anti- HCV positivity was found in one (0.2%) of the HBsAg-positive patients and anti-HIV positivity in the other (0.2%), concurrently. Anti-HIV positivity was detected in one patient. The risky behavior questionnaire determined that 522 (54.8%) of the participants had tattoos, 511 (53.6%) had a history of surgery, 384 (10.3%) had unprotected sexual intercourse, 256 (%26,9) had intravenous substance abuse behavior, and 35 (3.7%) had homosexual intercourse. Conclusion: The findings of our study show the current prevalence of hepatitis B, hepatitis C, and HIV in prisoners. It is important to detect index cases in prisons and to ensure that they receive treatment, both in the ward and after release, to prevent the spread of diseases in the community.